Can urinary histoplasma antigen test improve the diagnosis of histoplasmosis in a tuberculosis endemic region?. Issue 6 (21st March 2019) - Bansal, Nitin; Sethuraman, Nandini; Gopalakrishnan, Ram; Ramasubramanian, Venkatasubramanian; Kumar D, Suresh; Nambi P, Senthur; Chakrabarti, Arunaloke
Summary: Background: Many patients with histoplasmosis are treated with anti‐tubercular therapy (ATT) in tuberculosis endemic regions as diagnosis of histoplasmosis requires invasive sampling. We sought to study the utility of urinary Histoplasma antigen detection test. Methods: Case records of patients with a diagnosis of histoplasmosis prior to (Period A) and after (Period B) introduction of urinary Histoplasma antigen detection test were analysed in this single centre retrospective study. Results: Thirty‐seven patients (18 in Period A, and 19 patients in Period B) were studied. There was nearly a threefold increase in diagnoses (from 0.39 cases to 1.18 cases per month) after the introduction of antigen test. Nine patients (24.3%) were immunocompromised (6 had HIV infection and 3 were on steroids), and 28 (75.6%) were immunocompetent. Empirical ATT had been given to 10 patients prior to histoplasmosis diagnosis. Invasive tissue sampling was required in only two patients in Period B to confirm the diagnosis. Immunocompromised patients were younger, were more likely to have skin and mucosal findings, anaemia and leucopenia as compared to immune‐competent patients. Conclusion: This study emphasises that histoplasmosis cases may be missed and patients may receive ATT unnecessarily. Histoplasma antigen increased the diagnostic yield by almost threefold in our study.